Oil Prices and the Global Economy - Arezki, Rabah (IMF Working Papers; Working Paper ;, 2017)
This paper presents a simple macroeconomic model of the oil market. The model incorporates features of oil supply such as depletion, endogenous oil exploration and extraction, as well as features of oil demand such as the secular increase in demand from emerging-market economies, usage efficiency, and endogenous demand responses. The model provides, inter alia, a useful analytical framework to explore the effects of: a change in world GDP growth; a change in the efficiency of oil usage; and a change in the supply of oil. Notwithstanding that shale oil production today is more responsive to prices than conventional oil, our analysis suggests that an era of prolonged low oil prices is likely to be followed by a period where oil prices overshoot their long-term upward trend.